Sorafenib reduces steatosis-induced fibrogenesis in a human 3D co-culture model of non-alcoholic fatty liver disease - Romualdo, Guilherme Ribeiro [UNESP]; Da Silva, Tereza Cristina; de Albuquerque Landi, Marina Frota; Morais, Juliana Ávila; Barbisan, Luis Fernando [UNESP]; Vinken, Mathieu; Oliveira, Cláudia Pinto; Cogliati, Bruno (Wiley, 2020)
Non-alcoholic fatty liver disease (NAFLD) affects around 25% of the worldwide population. Non-alcoholic steatohepatitis (NASH), the more progressive variant of NAFLD, is characterized by steatosis, cellular ballooning, lobular inflammation, and may culminate on hepatic stellate cell (HSC) activation, thus increasing the risk for fibrosis, cirrhosis, and HCC development. Conversely, the antifibrotic effects of sorafenib, an FDA-approved drug for HCC treatment, have been demonstrated in 2D cell cultures and animal models, but its mechanisms in a NAFLD-related microenvironment in vitro requires further investigation. Thus, a human 3D co-culture model of fatty hepatocytes and HSC was established by culturing hepatoma C3A cells, pre-treated with 1.32 mM oleic acid, with HSC LX-2 cells. The fatty C3A/LX-2 spheroids showed morphological and molecular hallmarks of altered lipid metabolism and steatosis-induced fibrogenesis, similarly to the human disease. Sorafenib (15 μM) for 72 hours reduced fatty spheroid viability, and upregulated the expression of lipid oxidation- and hydrolysis-related genes, CPT1 and LIPC, respectively. Sorafenib also inhibited steatosis-induced fibrogenesis by downregulating COL1A1, TGFB1, PDGF, and TIMP1 and by decreasing protein levels of IL-6, TGF-β1, and TNF-α in fatty spheroids. The demonstration of the antifibrotic properties of sorafenib on steatosis-induced fibrogenesis in a 3D in vitro model of NAFLD supports its clinical use as a therapeutic agent for the treatment of NAFLD/NASH patients.
Keywords: antifibrotic therapy; fatty hepatocytes; hepatic stellate cells; non-alcoholic steatohepatitis; tridimensional cell culture